Metal complexes of crosslinked chitosans: correlations between metal ion complexation values and thermal properties - Trimukhe, K. D.; Varma, Anjanikumar (Carbohydrate Polymers, 2009)
A series of heavy metal complexes of crosslinked chitosans were evaluated by thermogravimetric studies. The metal complexes with Cu, Cd and Hg ions exhibiting the highest complexing ability to chitosans (Hg 354-364, Cu 100-112, and Cd 121-160, in mg/g chitosan), had the lowest onset of degradation temperatures (range 194-210 degrees C) and the lowest final degradation temperatures (generally less than 294-304 degrees C for Hg, 296-338 degrees C for Cu, and 305-368 degrees C for Cd complexes). Mn ion, with the lowest binding to chitosans (Mn 5-7 mg/g), showed the reverse behavior, having onset (240-248 degrees C) and final degradation temperatures (range 300-368 degrees C). Zn (binding 74-87 mg/g) and Pb (binding 39-62 mg/g) ions have a binding ability intermediate to Cu/Cd/Hg and Mn extremes, and therefore the effects on onset and final degradation temperatures are intermediate to these values. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chitosan; Crosslinked chitosan; Degradation temperature; Metal complexes; Thermal properties; Thermogravimetry